(untitled) (Scientific journal of the Fergana State University, 2025)
To obtain relatively high yields, special measures are required. Sands are poor in organic matter, which determines their unfavorable physical and chemical properties. Due to the rapid mineralization of organic matter and the leaching of nutrients from the arable horizon into deeper layers, the positive effect and aftereffect of fertilizers on such soils is limited.